Journal of technical education seience (Ho Chi Minh city University of Technology and Education, 2017)
Contents: The study of number and thickness of ingan/algan multiple quantum well structure for 365nm -385nm ultraviolet light-emitting diodes; Some new results in simulation of single electron transistor; Application pf isogeometric analysis to free vibration of truss structures;...